2010
DOI: 10.1016/j.procs.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Towards a user model for personalized recommendations in work-integrated learning: A report on an experimental study with a collaborative tagging system

Abstract: The informal setting of learning at work give rise for unique challenges to the field of technology enhanced learning systems. Personalized recommendations taking into account the current context of the individual knowledge worker are a powerful approach to overcome those challenges and effectively support the knowledge workers to meet their individual information needs. Basis for these recommendations to adopt to the current context of a knowledge worker can be provided by user models which reflects the topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Bozo et al [11] incorporate the teacher profile in their proposal, but build it on mostly demographic data. Schoefegger et al [17] apply heuristics to determine user work-related knowledge levels. This approach is interesting, but is based on knowledge topics that are professionspecific and, therefore, would require specific ontologies to capture teachers' actions.…”
Section: Recommender Systems In Telmentioning
confidence: 99%
“…Bozo et al [11] incorporate the teacher profile in their proposal, but build it on mostly demographic data. Schoefegger et al [17] apply heuristics to determine user work-related knowledge levels. This approach is interesting, but is based on knowledge topics that are professionspecific and, therefore, would require specific ontologies to capture teachers' actions.…”
Section: Recommender Systems In Telmentioning
confidence: 99%
“…The language was originally developed at the Open University of the Netherlands (OUNL) and is now IMS-Global standardized http://www.imsglobal.org/learningdesign/ increased opportunities for personalized learning will have a two-folded effect; reduction of delivery costs accompanied by more effective learning experiences, accelerating competence development, and increasing collaboration between learners. This matters in higher education as well as in workplace learning scenarios (Schoefegger, Seitlinger & Ley, 2010).…”
Section: Competences Experience Job Skills Learning Skillsmentioning
confidence: 99%
“…Other examples (e.g., Derntl, Günnemann, & Klamma, 2013;Southavilay, Yacef, Reimann, & Calvo, 2013) can be found that follow the knowledge creation metaphor, which deals with the collaborative and systematic development of common objects of activity. These LA applications model how learning materials and conceptual artifacts are collaboratively created (Schoefegger, Seitlinger, & Ley, 2010;Thüs, Chatti, Brandt, & Schroeder, 2015). The group of learners is taken as the unit of analysis, considering also their tools and common artifacts (Berendt, Vuorikari, Littlejohn, & Margaryan, 2014;Buckingham-Shum & Ferguson, 2012).…”
Section: Introductionmentioning
confidence: 99%